Sosialiasi Cabang Olahraga Arung Jeram Pada Pemuda Desa Babusalam - tofikin tofikin; Suhermon; Ferri Hendriyanto; Siska; Arisman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2025)
Abstract: White-water rafting is a water sport that combines elements of recreation, adventure, and physical and mental development. However, understanding of this sport among villagers, especially young people, remains low. A community outreach program was conducted in Babusalam Village to introduce white-water rafting as a means of character building, improving physical fitness, and developing the village's tourism potential. The program included outreach, demonstrations of basic rafting techniques, and interactive discussions with local youth. The results showed an increase in the knowledge, interest, and motivation of the youth of Babusalam Village to learn more about white-water rafting, both as a recreational activity and as an opportunity to develop sports achievements. Therefore, this outreach program is expected to be the first step in establishing a white-water rafting community that can support the development of both river-based sports and tourism in Babusalam Village.